Profitabilitas, Leverage, Ukuran Perusahaan, dan Tax Avoidance Pada Perusahaan Sektor Pertambangan - Karlina, Ayu; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 34 No 6 (2024)DO - 10.24843/EJA.2024.v34.i06.p19, 2024)
The objective of this study is to collect empirical evidence regarding the impact of profitability, leverage, and firm size on tax avoidance and to gather empirical data on how tax avoidance, profitability, and leverage differed before and during COVID-19 pandemic. This research performed on mining sector companies from 2018 to 2021 that registered on the Indonesia Stock Market. The sample was chosen using the purposive sampling method and 154 data were collected as observational objects. Multiple linear regression and different test was used to analyze the data. The findings revealed that profitability has positive effect on tax avoidance, leverage has no effect on tax avoidance, and firm size has negative effect on tax avoidance. Furthermore, the results of the different tests indicate that there is no significant average difference between profitability before and during pandemic. Meanwhile, the average difference in leverage between before and during COVID-19 is significant. The implication of this research is that it can confirm the Theory of Planned Behavior and Stewardship Theory. Keywords: Tax avoidance; Profitability; Leverage; Firm Size.